Prioritizing criteria and indicators for sustainable forest management: a case study on participatory decision making - Mendoza, G.A.; Prabhu, Ravi (Empresa Brasileira de Pesquisa Agropecuária, 2001)
This paper describes an application of the analytic hierarchy process (AHP) in assessing criteria and indicators (C&I) as measures of sustainable forest management. C&I elements are organised in hierarchical manner around the three general concepts, namely: Principle, Criteria and Indicators. These elements are prioritised based on their perceived relative importance values. These values are calculated using pairwise comparisons of the C&I elements following the principles of the AHP. Pairwise comparisons were obtained from experts representing various disciplines related to forest management. C&I analysis is done at different levels in the hierarchy. To demonstrate the method, a C&I assessment case study involves a forest located in Kalimantan, Indonesia. A generic set of C&I is used as a benchmark. AHP is used to calculate the relative weights of each C&I, prioritize them, and ultimately select a final set of C&I to be used in assessing the sustainability of the forest.